ANALISIS KEPENDUDUKAN DAN KESEJAHTERAAN EKONOMI DI NAGORI BOSAR: (STUDI TENTANG PEKERJA MIGRAN, PENDUDUK LOKAL DAN SUMBER PENDAPATAN) - Dian G Purba; Faisal Alviandi Siadari; Tommi Hermanto Damanik; Fahri I Siregar; Rospita C.Y Siahaan; Agustama Wani (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to analyze population and economic welfare in Nagori Bosar by focusing on the differences between residents who work outside the village (migrant workers) and those who continue to work within the village. This study uses simple research by collecting data through short interviews conducted directly with the village head of NAGORI BOSAR. The research results show that 40% of Nagori Bosar residents work outside the village, while the other 60% work inside the village. Migrant workers tend to have higher income levels compared to local residents who work in villages. However, economic prosperity is not only determined by income but also by access to health, education and infrastructure facilities. This research also found that poverty and unemployment rates in Nagori Bosar are still high, especially among residents who do not have permanent jobs. The source of income for the people in this village is dominated by the agricultural, small trade and service sectors. Overall, this research reveals that although labor migration makes a significant contribution to increasing family income, there is an urgent need to improve the well-being of local residents through improving infrastructure and increasing access to basic services. The implications of this research indicate the need for more targeted policy interventions to reduce poverty and unemployment in Nagori Bosar.